So sánh hệ thống từ xưng hô trong tiếng Việt và trong tiếng Pháp - Nguyễn, Vân Dung (H. : ĐHQGHN, 2017)
The employment of vocatives is one of the important factors in conversational strategics. Participants in a conversation usually try to show th at they are well- acquainted with their interlocutors partly by using appropriate vocatives. That is why, basic as well as comparative research into vocative systems of the foreign language being learnt . Within the framework of this article, a comparison between the vocative systems in Vietnamese and French will be provided so as to bring about the similarities and differences between the two languages via verbal communication.